Utilization of the Metaverse World in Islamic Religious Education Learning for Ease of Islamic Mosaic Exploration - Muhammad Abdul Ilah (Al-Qalam Institue, 2026)
This study aims to examine the potential of metaverse-based learning in facilitating the exploration of the Islamic mosaic and enhancing students’ understanding within Islamic Religious Education (Pendidikan Agama Islam, PAI). Employing a qualitative case study approach, the research involved purposively selected students participating in PAI courses. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed using coding, thematic analysis, and interpretative techniques. The findings reveal that the integration of the metaverse creates an interactive and immersive learning environment that supports students’ engagement with the diverse and complex dimensions of Islamic teachings. From an educational management perspective, effective instructional planning, learning organization, and the facilitative role of PAI teachers were found to be crucial in optimizing metaverse utilization. Furthermore, the metaverse encourages reflective learning and collaborative interaction, contributing to deeper religious understanding. The study implies that the strategic management of digital learning environments is essential to ensure that metaverse-based PAI learning remains pedagogically effective and value-oriented. These findings offer practical insights for educators and institutions in developing innovative and well-managed Islamic Religious Education models in the digital era.